Pengaruh Penggunaan Metode Pembelajaran Penemuan Terbimbing Terhadap Motivasi Belajar Fisika Peserta Didik SMA Negeri 3 Kota - Asyhari A. Usman; Faradina Faradina (Peneliti.net, 2022)
The research is quantitative research by using quasi experiment with posttest- only control group design which aims to analyze (1) the difference of physics learning motivation of students who were taught by using guided discovery learning method and the ones who were taught by using conventional method at SMAN 3 Kota Ternate of academic year 2021/2022, The data of the research were collected in three stages, namely 1) the preparation stage which covered initial observation to the samples of the research and the making of learning devices and learning instruments including content and empiric validation, 2) the implementation stage in forms of giving physics learning motivation questionnaire, the utilization of guided discovery learning method in experiment class, and utilization of conventional method in control class, 3) the final stage by giving posttest which then alayzed for hypothesis test. The data of the results of the research were processed descriptively and inferentially to describe the students physics leraning motivation and science process skills. The results of descriptive analysis reveal that the average score of Physics learning method is 16,14 from the ideal score 83 and deviation standard 6,00. While the average score of Physics learning motivation of the students who were taught by using conventional method is 60,08 from the ideal score 75 and deviation standar 47,67. There significant difference of Physics learning motivations of the students who were taught by using guided discovery learning method with the students who were taught by using conventional method class X student at SMAN 3 Kota Ternate of academic year 2021/2022.